2003
DOI: 10.1007/s10350-004-7291-9
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Patients Undergoing Liver Transplantation for Primary Sclerosing Cholangitis

Abstract: The activity of inflammatory bowel disease after transplantation is highly variable. Patients appeared to lack knowledge of their increased risk for colorectal neoplasia. Colorectal cancer is an uncommon but important complication in patients after liver transplantation for primary sclerosing cholangitis, and ongoing surveillance is required. Patients may require education to increase their awareness of the cancer risk and compliance with surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 34 publications
(49 reference statements)
0
13
1
Order By: Relevance
“…32 Previous studies, however, have been contradictory and reported a favorable as well as a more aggressive course of IBD in PSC patients after liver transplantation. 5,[32][33][34][35] These studies compared IBD activity before and after transplantation in the same patients and may not be directly comparable to the present cross-sectional study of two parallel patient cohorts.…”
Section: Discussioncontrasting
confidence: 48%
“…32 Previous studies, however, have been contradictory and reported a favorable as well as a more aggressive course of IBD in PSC patients after liver transplantation. 5,[32][33][34][35] These studies compared IBD activity before and after transplantation in the same patients and may not be directly comparable to the present cross-sectional study of two parallel patient cohorts.…”
Section: Discussioncontrasting
confidence: 48%
“…However the natural history of UC following liver transplantation is variable [68][69][70][71][72] . One study showed approximately a third had improvement in colitis, a third remained unchanged and a third suffered increased activity of colonic disease [73] . Several series report increased rates of colon cancer and colectomy after liver transplantation [74][75][76] .…”
Section: Psc Treatmentmentioning
confidence: 99%
“…Conflicting reports of IBD activity have been published regarding the impact of a liver transplant on patients with preexisting IBD [192][193][194][195][196]. Risk factors for worsening of preexisting IBD after liver transplant includes active bowel inflammation at the time of transplantation [193], short interval between diagnosis of IBD and transplant [193], cigarette smoking [197], Clostridium difficile infection [198] and use of Tacrolimus after transplant [191,193,199,200].…”
Section: Ibd and Liver Transplantationmentioning
confidence: 99%
“…Risk factors for worsening of preexisting IBD after liver transplant includes active bowel inflammation at the time of transplantation [193], short interval between diagnosis of IBD and transplant [193], cigarette smoking [197], Clostridium difficile infection [198] and use of Tacrolimus after transplant [191,193,199,200]. The use of steroid or immunosuppressive agents prior to transplant does not predict post-transplant IBD activity [194,195]. Steroids, Azathioprine and Cyclosporine should be preferred in these subgroup of patients [94,193,[199][200][201].…”
Section: Ibd and Liver Transplantationmentioning
confidence: 99%